Designing A Website-Based Spice and Spice Sales Application using the Prototype Method - Azizi, Faziz (Information Technology and Systems, 2024)
Online marketplaces have become one of the main platforms in modern commerce, facilitating accessibility and convenience for consumers to purchase goods online. In this context, this study aims to design a website-based application for selling herbs and spices using the prototype method. This method was chosen because it allows developers to iteratively develop the features of the application based on feedback from users. This research describes the process of designing a website-based application with a focus on optimal user experience. Through the stages of needs analysis, conceptual design, and prototype implementation, this application was developed to meet the needs of users in shopping for herbs and spices online. Users will have easy accessibility through an intuitive and responsive interface, as well as features such as product search, shopping cart, and secure payment processing. The results of this research are expected to contribute to the development of e-commerce, especially in the sales sector of herbs and spices. By utilizing the prototype method, developers can identify user needs more effectively and produce applications that are more in line with market expectations. In addition, this research can also be a foundation for advanced research in the development of more complex and integrated e-commerce applications.